2018
DOI: 10.1016/j.apmr.2017.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial to Examine the Impact of Aquatic Exercise Training on Functional Capacity, Balance, and Perceptions of Fatigue in Female Patients With Multiple Sclerosis

Abstract: Aquatic exercise training improved functional capacity, balance, and perceptions of fatigue in women with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 45 publications
1
65
0
12
Order By: Relevance
“…There are several preliminary studies regarding the effects of exercise on fatigue reduction in MS patients. In a recent study conducted in Iran [15], the mean fatigue score before exercise was 1.43 and after exercise 8.32. In a similar study in Ireland [16], these scores were respectively 3, and 20.…”
Section: Introductionmentioning
confidence: 92%
“…There are several preliminary studies regarding the effects of exercise on fatigue reduction in MS patients. In a recent study conducted in Iran [15], the mean fatigue score before exercise was 1.43 and after exercise 8.32. In a similar study in Ireland [16], these scores were respectively 3, and 20.…”
Section: Introductionmentioning
confidence: 92%
“…22 To encourage a comparable mental set, patients should undergo an initiation sessions in an attempt to familiarize to sensations and to what is considered a visibly good muscle. 23 The most important differences between this suggested hypothesis with previous studies is related to progressive pattern of cycling, as most of the previous studies, used a fixed duration of cycling and as such, made the therapeutic process longer. Based on this hypothesis, concurrent cycling training and FES would result in superior improvements in cycling performance, aerobic capacity, and functional performance in post-stroke patients as a result of an increased activation of cortical regions.…”
Section: Discussionmentioning
confidence: 86%
“…Most of the studies that have used aquatic exercises to improve balance in different communities have only considered static and dynamic balance indices, and recovery strategy as the most important factor in maintaining and recovering balance. The most important cause of falling in individuals has received less attention [30,[33][34][35]. Beyranvand et al reported no effect of aquatic exercises on improving the balance strategy in elderly men; only the static and dynamic balance of elderly men improved after an 8 weeks of aquatic exercises, in their research [21].…”
Section: Discussionmentioning
confidence: 99%
“…All the training exercises were first taught to the subjects by the examiner, then they were asked to perform practical trials [28]. The body weight is reduced to 40%-51% after Anterior Superior Iliac Spine (ASIS) level of immersion in the pool [30]. In the first week, the WV group performed the exercises without any additional weight and only by wearing vests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation